2014
DOI: 10.1111/1471-3802.12056
|View full text |Cite
|
Sign up to set email alerts
|

‘They think that if you're a teacher here … you're not clever enough to be a proper teacher’: the courtesy stigma experienced by teachers employed at schools for pupils with behavioural, emotional and social difficulties (BESD)

Abstract: A wealth of literature has identified that children with behavioural, emotional and social difficulties (BESD) and their families are frequently stigmatised due to the perceived controllable and ‘invisible’ nature of this special educational need (SEN). Yet little research has considered the impact of this stigma on another group of individuals, educational practitioners employed in BESD schools. This is despite these professionals working in close contact with pupils with BESD, a heavily stigmatised group, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, teachers in special schools can also experience stigma. Broomhead () explored the stigma attached to the educational practitioner employed in BESD schools using interviews with six headteachers and three class teachers in BESD schools. She concluded that practitioners in BESD schools may not be perceived as ‘proper’ teachers due to the discourse of care surrounding them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, teachers in special schools can also experience stigma. Broomhead () explored the stigma attached to the educational practitioner employed in BESD schools using interviews with six headteachers and three class teachers in BESD schools. She concluded that practitioners in BESD schools may not be perceived as ‘proper’ teachers due to the discourse of care surrounding them.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, research highlighting the benefits and challenges faced by special schools is investigated (Hornby & Witte, 2008;Parsons et al, 2009;Parsons, 2015;Day et al, 2012;Reed et al, 2012;Kelly et al, 2014;Black, 2014;Cook et al, 2016). Thirdly, research emphasising the value and challenges of inclusion in mainstream settings is reviewed (Frederickson et al, 2007;Lindsay et al, 2016;O'Hagan & Hebron, 2016;Broomhead, 2013Broomhead, , 2014de Graaf et al, 2013;Waddington & Reed, 2016;de Boer et al, 2013;Glazzard, 2014;Webster & Blatchford, 2015). Research that listens to the voice of 'disabled' and 'non-disabled' children regarding mainstream and special school provision is the final theme (Griffiths, 2007;Prunty et al, 2012;Gasson et al, 2015;Geordiadi et al, 2012;Tuersley-Dixon & Frederickson, 2016;Roberts & Simpson, 2016;Feiler, 2013;Skovlund, 2014).…”
mentioning
confidence: 99%
“…Such 'courtesy stigma' has been documented in other fields. For example Broomhead (2016) documented how teachers employed by schools for pupils with behavioural, emotional and social difficulties felt stigmatised and treated as if they were not as clever as other teachers.…”
Section: The Need To Privilege the Voices Of Other Relevant Stakeholdersmentioning
confidence: 99%
“…Courtesy stigma can also be projected onto professionals who work with a stigmatised group. For example, Broomhead (2016) explored how teachers in special needs education are not considered as “proper” teachers.…”
mentioning
confidence: 99%